Numerical Analysis on Steam Exciting Force Caused by Rotor Eccentricity - L. H. Cao; J. X. Wang; P. Li; P. F. Hu; Y. Li (Shock and Vibration)
The steam exciting force has been proved to be great threat to the operation safety of steam turbines. The mechanism of steam exciting vibration cannot be profoundly revealed by simply analyzing the steam exciting force, especially in simplified models. Therefore, a full-circle stage of steam turbine with shroud and labyrinth seals was investigated by numerical simulator CFX. The instability of leakage flow and the pressure fluctuation were analyzed on the eccentric condition. The effects of leakage vortexes, the depth-width ratio of seal cavity, and the eccentricity on the steam exciting force were studied. Results show that the leakage flow is nonuniform in the circumferential direction with the change of front teeth vortexes, which causes the steam exciting force. The tangential and radial steam exciting force both increase with the eccentricity increasing. The effects of the depth-width ratio of seal cavity on the two forces are different. In addition, the pressure fluctuation caused by the leakage vortexes on the shroud surfaces is a main factor inducing the steam exciting force. This research provides a theoretical guidance for the operation safety and optimization of steam turbines.